Maspin Gene Expression in Invasive Ductal Carcinoma of Breast - Shahriar Dabiri; Mohammadmehdi Moeini aghtaei; Jahanbano Shahryari; Manzume Shamis meymandi; Sahar Amirpour-Rostami; Reza Foutohi-Ardekani (Iranian Society of Pathology, 2016)
Background: The breast cancer is the most prevalent cancer among women, on the other hand absence of myoepithelial cells play a pivotal role in pathogenesis of this cancer. Thus we aimed to investigate the possible abilities of the molecular assay technique to find a relationship between mammary serine protease inhibitor (Maspin) gene expression possibly secreted by myoepithelial cells, grade of breast cancer and other prognostics factors (ER, PR, and c-erb-B2). Methods: Paraffin embedded blocks of 31 breast cancer patients together with two normal breast tissues were used for IHC staining and Maspin gene RNA detection uses the real-time PCR method. Applying QIAGEN kit, we were able to measure Maspin RNA and Extract the cDNA of different samples for evaluating the Maspin RNA level. Results: We found that the RNA level was considerably lowerin these cancer samples compared with normal samples. In addition, different grades of breast cancer in the obtained results adopt some distinguishable values. The Maspin expression in samples with grades II and III is much lower than the ones in normal group (P<0.05) which could be considered as a promising way in diagnosing of this disease. The results showed no considerable differences in Maspin gene expression of the c-erb-B2 scores in the tumor group except the samples having score 0. The other observation of this research study confirmed that Maspin gene expression couldn't show any differences between the values of both ER and PR in different scores of the tumor group. On the other hand, the cDNA of these patients showed lower values compared with normal samples. Conclusion: Maspin expression was reduced in samples with grade II& III of invasive ductal carcinoma. Based on expression of Maspin Inc-erb-B2, it seems that more expression happened in normal group comparing with different scores of it. We could suggest that there was a reverse relationship between tumor formation and Maspin gene expression. These results showed possible role of Maspin as prognostic factor.